Pengaturan Penyusunan Proyek Perubahan Pendidikan dan Pelatihan Kepemimpinan (Studi Kasus Penyusunan Proper Diklatpim III dan IV di Daerah Provinsi): Arrangement of Project Arrangement for Changing Leadership Education and Training (Case Study of Proper Preparation of Diklatpim III and IV in Provincial Areas) - Daulay, Syahrin (Anterior Jurnal, 2019)
In order to achieve national goals, it is required civil servant which are professional, free from political intervention, corruption, collusion, and nepotism functioned as public services, adhesive and unifying nation. The efforts that must be made to realize such competencies, is civil servant must take part in leading educational and training (diklatpim). National Institute for Public Administration of the Republic of Indonesia has released diklatpim regulation level III and level IV. The competence that must be built is visioner leadership that able to cooperate with other strategic stakeholders to manage those national strategic issues to achieve national goals. However, the number of alumni that enrolled to participate in innovation competition after diklatpim and Kalimantan Innovation Jamboree 2018 was only 12 participants. The reason for the small number of alumni to enroll in those competitions amongst others were mutations, the selected issues were not accommodated in the planning and budgeting documents, and not in the best ten of the rank. Some problems associated with conducting the PoC are that the selected issues are not strategic in the PB documents, schedule of diklatpim is not in line with the agenda of the provincial government, organization structure and the sequences of activities are designed improperly, and also the implementation of those activities are not based on good governance principles. The paper will discuss how the arrangement and implementation of the preparation of the PoC in diklatpim now and to recommend the preparation method of the PoC of diklatpim in the provincial government level.